Thank you for the opportunity to help you with your question!
According to the question,
3(x^2) -1 =0
So, to solve it, we first add 1 to both sides of the equation. This gives
=> 3(x^2) -1 +1 = 1
=> 3(x^2) =1
Now, dividing both sides of the equation by 3 gives,
=> (x^2)= (1/3)
Now finally, taking the square root of both the sides gives,
=> x= + sqrt(1/3)
Hence, the value of x in + sqrt(1/3). This can also be written as x= + sqrt(3)/3.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?